Development of a Foundation Phase Curriculum based on Multiple Intelligences Integrated with Technology Content and Local Wisdom - Akhmad Rudi Masrukhin; Finadatul Wahidah; Umah Amrela; Zety Yusmira (Cita konsultindo, 2023)
The theory of multiple intelligences was first introduced by Howard Gardner in 1983 in his book Frames of Mind: The Theory of Multiple Intelligences. This theory proposes that intelligence cannot only be measured by one IQ test but that there are many different types of intelligence. As an educator or parent, it is important to recognize what intelligence is dominant in AUD and provide learning experiences that suit the child's intelligence. This will help AUD develop optimally in various aspects of his intelligence. Curriculum development is a cyclical process that never has a starting point or an endpoint because curriculum development is a process that relies on elements in the curriculum, which include objectives, methods and materials, assessment and feedback. The stages of curriculum development include goal setting, material selection, curriculum writing, curriculum implementation, and evaluation of ongoing implementation. This research was conducted at the Jember Regency PAUD institution. The approach used is qualitative with a case study type of research. The techniques used are observation, interviews and documentation. The results of this research are that curriculum development begins with characteristics analysis and needs analysis. This is done to formulate a vision, mission and goals. Next, strategies are prepared to achieve the goals. Organize the Intracurricular, Extracurricular and P5 PPRA curriculum in the foundation phase curriculum. From organizing the learning, the learning outcomes are described into topics, sub-topics and sub-subtopics. From the results of the translation into sub-topics, learning plans and teaching modules are then prepared. The learning plan that will be implemented will be based on multiple intelligences and integrated with technology content and local wisdom. The final stage is an evaluation carried out reflectively.